An Elementary Chapter in Number Theory: Proof of Fermat’s Last Theorem (Indian Journal of Advanced Mathematics (IJAM), 2025)
Pierre de Fermat first stated around 1637 that for any integer n > 2, the equation an + bn = cn has no positive integer solutions, and he said the theorem in the margin of a copy of Arithmetica. His proof is available only for the equation a 4 + b 4 = c 4 for the exponent n = 4. Subsequently, Euler proved the theorem in the equation a 3 + b 3 = c 3 for the exponent n = 3. Taking the above two proofs of Fermat and Euler, it would suffice to prove the theorem for n = p, where p is any prime > 3. In this proof, we hypothesize all r, s and t as positive integerssatisfying the equation rp + sp = tp and establish a contradiction. We use another auxiliary equation, x 3 + y 3 = z 3 , and combine the two equations using transformation equations. Solving the transformation equations, we establish a contradiction, thereby proving the theorem.